Which health and biomedical topics generate the most Facebook interest and the strongest citation relationships?. Issue 3 (May 2020) - Mohammadi, Ehsan; Gregory, Karl B.; Thelwall, Mike; Barahmand, Nilofar
Highlights: Four biomedical areas, including general and internal medicine and complementary and alternative medicine receive more Facebook attention. No biomedical areas receive little Facebook attention. The relationship between Facebook mentions and citations varies by field and public interest. Facebook mentions predict future citations less well for fields with variable public interest. Abstract: Although more than a million academic papers have been posted on Facebook, there is little detailed research about which fields or cross-field issues are involved and whether there are field or public interest relationships between Facebook mentions and future citations. In response, we identified health and biomedical scientific papers mentioned on Facebook and assigned subjects to them using the MeSH and Science Metrix journal classification schema. Multistage adaptive LASSO and unpenalized least-squares regressions were used to model Facebook mentions by fields and MeSH terms. The fields Science and Technology, General and Internal Medicine, Complementary and Alternative Medicine, and Sport Sciences produced higher Facebook mention counts than average. However, no MeSH cross-field issue differences were found in the rate of attracting Facebook mentions. The relationship between Facebook mentions and citations varies between both fields and MeSH cross-field issues. General and Internal Medicine, Cardiovascular System and Hematology and Developmental Biology have strongest correlations between Facebook mentions and citations, probably due to high citation rates and high Facebook visibility in these areas.